2014
DOI: 10.7314/apjcp.2014.15.19.8007
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Features of Cytotoxic Activity of Flavonoids on Human Cervical Cancer Cells

Abstract: Cervical cancer is the most common gynecologic malignancy worldwide and development of new therapeutic strategies and anticancer agents is an urgent priority. Plants have remained an important source in the search for novel cytotoxic compounds and several polyphenolic flavonoids possess antitumor properties. In this review article, data about potential anticarcinogenic activity of common natural flavonoids on various human cervical cancer cell lines are compiled and analyzed showing perspectives for the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 108 publications
1
12
0
Order By: Relevance
“…Allocation of the initial hit compounds into clusters based upon structural similarity revealed that the biggest cluster comprised flavonoid compounds. This finding was consistent with the literature, because most compounds that have been discovered thus far as E6 inhibitors have a flavonoid chemotype [32]. In fact, 8 of the compounds identified as initial hits in our study had already been published as E6 specific inhibitors.…”
Section: Discussionsupporting
confidence: 93%
“…Allocation of the initial hit compounds into clusters based upon structural similarity revealed that the biggest cluster comprised flavonoid compounds. This finding was consistent with the literature, because most compounds that have been discovered thus far as E6 inhibitors have a flavonoid chemotype [32]. In fact, 8 of the compounds identified as initial hits in our study had already been published as E6 specific inhibitors.…”
Section: Discussionsupporting
confidence: 93%
“…More than ten polyphenolic flavonoids, such as quercetin, catechin, luteolin, rutin and hesperidin, have been reported to possess cytotoxic and antitumor properties ( 9-11 ). Their anticancer effects primarily include antioxidant activity, promotion of apoptosis, inhibition of proliferation, migration, invasion and angiogenesis, modulation of signal transduction pathways and reversal of drug resistance ( 8 , 12 ). Evidence has demonstrated that wogonoside (wogonin-7-glucuronide, C 22 H 20 O 11 ), a primary component of the Traditional Chinese Medicine Scutellaria baicalensis , induces apoptosis and cell cycle arrest in multiple types of tumor cells, such as non-small cell lung cancer, hepatocellular carcinoma and chronic myelogenous leukemia cells ( 13-15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are widely found in plants in nature and are secondary metabolites of plants (Sak, 2014), and has antioxidant activity, anticancer, anti-inflammatory (Jin et al, 2010, Rokayya et al, 2014, Jantrawut et al, 2017), hepatoprotective potential and antibacterial activity. Recently, the vegetables, fruits and plants that contain a substantial number of flavonoid compounds have received more and more attention for their medical utility.…”
Section: Introductionmentioning
confidence: 99%